2021
DOI: 10.1094/pdis-10-20-2318-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Postharvest Stem End Rot Disease on MD2 Pineapple Fruits Caused by Neoscytalidium dimidiatum in Malaysia

Abstract: Repeated sampling conducted from December 2019 to March 2020, and fruit of pineapple (Ananas comosus) var MD2 showing early stem end rot symptoms including brown and rotten fruit skin near the stem end region (Fig.1Aa) or darker skin with black discoloration (Fig.1Ab) indicated a consistent fungal infection. The samples (30 fruits from each location) were collected from store houses in three farmer fields with 60% disease incidence in Serdang, (3.0220oN,101.7055oE), Selangor, West Malaysia. The pulp of infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“… Fabaceae Acacias Chandra ( 1974 ) Albizia lebbeck Fabaceae Siris tree Elshafie and Ba‐Omar ( 2002 ) Agave sp. Asparagaceae Kranz ( 1963 ) Agave sisalana Asparagaceae Sisal Xie et al ( 2021 ) Anacardium occidentale Anacardiaceae Cashew Coutinho et al ( 2018 ) Ananas comosus Bromeliaceae Pineapple Kuruppu et al ( 2021 ) Arachnis sp. Orchidaceae Scorpion orchid Williams and Liu ( 1976 ) Araucaria sp.…”
Section: Appendix a – Neoscytalidium Dimidiatum Ho...mentioning
confidence: 99%
“… Fabaceae Acacias Chandra ( 1974 ) Albizia lebbeck Fabaceae Siris tree Elshafie and Ba‐Omar ( 2002 ) Agave sp. Asparagaceae Kranz ( 1963 ) Agave sisalana Asparagaceae Sisal Xie et al ( 2021 ) Anacardium occidentale Anacardiaceae Cashew Coutinho et al ( 2018 ) Ananas comosus Bromeliaceae Pineapple Kuruppu et al ( 2021 ) Arachnis sp. Orchidaceae Scorpion orchid Williams and Liu ( 1976 ) Araucaria sp.…”
Section: Appendix a – Neoscytalidium Dimidiatum Ho...mentioning
confidence: 99%
“…These fungal pathogens are considered important as they do not only attack leaves but also other pineapple plant parts such as butt (C. paradoxa) and fruits (Fusarium spp.). Recently, Kuruppu et al (2020) reported that the fungus Neoscytalidium dimidiatum can cause stem-end rot of pineapple particularly on pineapple MD2 variety in Malaysia. In our research (unpublished data), this fungal pathogen can also cause brown leaf spot disease on pineapple leaf and fruitlet rot on pineapple fruit (Figure 1).…”
Section: Causal Pathogenmentioning
confidence: 99%
“…Normally, the colour of the infected area turns cream or almost white, but the margins of the spot often remain brown (Figure 1). This fungal pathogen also causes stem-end rot disease and the disease symptoms have been explained by Kuruppu et al (2020) as brown and rotten fruit skin near the stem end region or darker skin with black discolouration.…”
Section: Causal Pathogenmentioning
confidence: 99%
“…The distribution of this genus has extended to all continents. Neoscytalidium genus can influence the different parts of plants by causing diseases that show various symptoms on aerial and underground parts of hosts, including shoot blight canker and gummosis (Polizzi et al, 2009), dieback (Ray et al, 2010), collar and root rot (Machado et al, 2012), brown spot (Lan et al, 2012), death of graft (Chen et al, 2013), internal black rot (Ezea et al, 2013), shoot and needle blight (Türkölmez et al, 2019a), tuber rot (Derviş et al, 2020a), root and stem rot (Oksal and Ozer, 2021;Kuruppu et al, 2021), stem-end rot (Li et al, 2021), sooty canker (Yeganeh and Mohammadi, 2022), and leaf scorch (Table 1). Members in the genus Neoscytalidium have been reported as pathogenic agents on various crops and trees, such as almond (Prunus dulcis), Avicennia marina Forssk., baobab (Adansonia gibbosa), bardi bush (Acacia synchronica), blue grevillea (Grevillia agrifolia), rattlepod (Crotalaria medicaginea), olive (Olea europaea L.), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Members in the genus Neoscytalidium have been reported as pathogenic agents on various crops and trees, such as almond (Prunus dulcis), Avicennia marina Forssk., baobab (Adansonia gibbosa), bardi bush (Acacia synchronica), blue grevillea (Grevillia agrifolia), rattlepod (Crotalaria medicaginea), olive (Olea europaea L.), etc. (Table 1), causing economic yield losses (Pavlic et al, 2008;Ray et al, 2010;Sakalidis et al, 2011;Rahmani, 2018;Chakusary et al, 2019;Sabernasab et al, 2019;Derviş et al, 2019;Mello et al, 2019;Türkölmez et al, 2019;Brito et al, 2020;Alananbeh et al, 2020;Oksal and Ozer, 2021;Kuruppu et al, 2021;Oren et al, 2022;Yeganeh and Mohammadi, 2022;. Though, they have also been reported as opportunistic human pathogens causing chronic superficial infections of skin, nails, and nose, cutaneous, invasive cutaneous, deep cutaneous infection, onychomycosis, dermatomycosis, fingernail onychomycosis, superficial black onychomycosis, rhinosinusitis, brain abscess, and pulmonary disease (Bakhshizadeh et al, 2014;Dionne et al, 2015;Yang et al, 2019;Jo et al, 2020;González Cortés et al, 2021;Raiesi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%